2011
DOI: 10.2527/jas.2010-3246
|View full text |Cite
|
Sign up to set email alerts
|

The effect of different postweaning altrenogest treatments of primiparous sows on follicular development, pregnancy rates, and litter sizes1

Abstract: This study investigated follicular development during and after postweaning altrenogest treatment of primiparous sows in relation to subsequent reproductive performance. Primiparous sows (n = 259) were randomly assigned at weaning (d 0) to 1 of 4 groups: control (no altrenogest, n = 71), RU4 (20 mg of altrenogest from d -1 to 2, n = 62), RU8 (20 mg of altrenogest from d -1 to 6, n = 65), or RU15 (20 mg of altrenogest from d -1 to 13, n = 61). Average follicular size (measured by ultrasound) increased during al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 31 publications
3
25
1
1
Order By: Relevance
“…Ovary scanning was conducted according to the procedures described earlier [23]. The ovaries of the sows were monitored using transabdominal ultrasound scans performed with a sectorial probe (5 MHz, MS Multiscan digital, MS Schippers, The Netherlands) to estimate the average follicle size.…”
Section: Follicle Sizementioning
confidence: 99%
“…Ovary scanning was conducted according to the procedures described earlier [23]. The ovaries of the sows were monitored using transabdominal ultrasound scans performed with a sectorial probe (5 MHz, MS Multiscan digital, MS Schippers, The Netherlands) to estimate the average follicle size.…”
Section: Follicle Sizementioning
confidence: 99%
“…Even though previous studies revealed improved fertility of the sows that were treated with ALT was a consequence of better follicular development, especially increasing follicular size (11)(12)(13), the effect of ALT on the homogeneity of preovulatory follicles was not mentioned. Since follicular diversity is associated with the diversity of embryonic development and survival during early pregnancy (1,6), there is a need to investigate homogeneity of preovulatory follicles for better fertility in sows.…”
Section: Introductionmentioning
confidence: 99%
“…After weaning, the production and release of OT are stimulated by estradiol produced from follicles (Carter, ; Gimpl & Fahrenholz, ; Wathes et al., ), which is supported by increasing gonadotrophin stimulation, particularly by FSH and LH (Kemp, Soede, & Langendijk, ; Van den Brand, Dieleman, Soede, & Kemp, ; Van Leeuwen et al., ). The positive relationship between follicular development and estradiol concentrations during the follicular phase was confirmed by several studies (Breuel et al., ; Nayudu & Osborn, ; Sheldon & Dobson, ).…”
Section: Introductionmentioning
confidence: 99%